Study on Thermo-Structural Coupling Mechanism and Multi-Field Evolution Law during the Firing Process of Ceramic Slabs - Wang, Xianewei; Xu, Wenlong; Yu, Hailong; Li, Chenyang; Zhao, Haikuo; Feng, Yihang; Fang, Caiqi; Zhang, Heng; Xu, Aihua; Xie, Wentao; Li, Xiulian (Manufacturing Technology Journal, 2026)
To address cracking and deformation in large-size ceramic slabs during firing induced by thermo-structural coupling, this study established an indirect thermo-structural coupling finite element model in Ansys to analyze an 820 mm*100 mm*6.32 mm slab. The evolution of temperature field, stress field, and deformation was investigated across four firing stages. Results indicate that the rapid cooling stage, with a high convective heat transfer coefficient, forms the cycle's maximum thermal gradient, showing the most asymmetric temperature field of mid-plane high, surfaces low and a ~17°C surface-mid-plane temperature difference. The stress field follows a low-high-declining-stable trend, peaking in rapid cooling of 23 MPa maximum equivalent stress in the thickness section and 11 MPa maximum principal stress at the glaze-body interface. Thermal gradient, glaze-body CTE mismatch, and boundary constraints respectively drive stress generation, interface concentration, and asymmetric distribution. Deformation obeys length > width > thickness in rapid cooling, lengthwise deformation is 8.2 times the width. Thickness-direction drum-shaped deformation stems from glaze-body CTE mismatch. This study reveals the firing thermo-structural coupling mechanism, providing theoretical support for optimizing firing processes and glaze-body formulations, with significant engineering value for reducing cracking and improving dimensional stability.
Keywords: Ceramic slab; Thermo-structural coupling; Firing deformation; Maximum principal stress